Impact of cardiac magnetic resonance imaging on heart failure patients referred to a tertiary advanced heart failure unit: improvements in diagnosis and management. Issue 2 (12th February 2019) - Lum, Ying H.; McKenzie, Scott; Brown, Martin; Hamilton‐Craig, Christian
Abstract: Background: The clinical use of cardiac magnetic resonance (CMR) in Australian heart failure (HF) patients has limited evidence. Aim: To examine how CMR, compared with routine echocardiography, affects the diagnosis and management of patients with HF. Methods: Single‐centre retrospective study of HF patients newly referred to the Advanced Heart Failure and Transplant unit at The Prince Charles Hospital, Brisbane. Between January 2010 and December 2014, all patients clinically referred for both CMR and echocardiography in the workup of HF were analysed. Imaging results, electronic records and medical charts were reviewed for final diagnosis and changes in clinical management. Results: A total of 114 new HF referrals was included. Evaluation of HF of uncertain aetiology (70%) was the most common indication for CMR. In 20% of cases, CMR led to a completely new diagnosis or diagnostic confirmation of suspicions raised by echocardiography. Clinical decision‐making was altered in 48%, with the greatest impact on decisions regarding revascularisation. Overall, CMR had a significant impact on 50% of patients. In a multivariable model, the only independent variable significantly associated with clinical impact was the presence/absence of late gadolinium enhancement ( P < 0.001). Importantly, body mass index, echocardiography image quality and the presence of sinus rhythm did not show statistical significance in the multivariate analysis. Conclusion: CMR makes a substantial contribution to both the diagnosis and management of HF patients over and above standard echocardiography. This study provides evidence of its clinical utility in the HF population in Australia and supports the role of CMR in the routine assessment of this cohort.